Adaptive SWE and SNMP-based sensor management for environmental monitoring. (1st January 2014) - Dow, Chyi-Ren; Lee, Yu-Hong; Hu, Ruei-Yu
Environmental monitoring technologies and applications have developed rapidly because of growing interest in environmental issues. Previous research on environment monitoring can be divided into two major categories: sensing data collection and heterogeneous system integration. With the improvement of sensing devices, the operational condition of a device is also regarded as environmental information. This study proposes a sensor web enablement (SWE) and simple network management protocol (SNMP)-based management framework. The proposed framework defines the entity management information base (MIB) of debris-flow sensors to integrate the management of various debris-flow sensors. An administrator can describe an object and its attributes to construct the tree-based SWE management architecture. This framework provides dynamically managed objects and standardises the message management between the management system and sensors. Data access and collection are based on the SWE standard message format, which enhances the exchangeability of sensing data. The proposed system integrates the SWE and SNMP services into a web service-based interface that provides real-time, seamless, and remote management services. The proposed system also provides dynamic monitoring functions for different rainfall events.